2014
DOI: 10.1111/ases.12158
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative circulatory management using the FloTracTM system in laparoscopic liver resection

Abstract: The average SVV value during laparoscopic liver transection (mean, 17.0%) exceeded the conventional cut-off value, but in this study, no perioperative complications developed, which enabled safe management. We might be able to manage appropriate fluid control using FloTrac system in patients with laparoscopic liver resection. Therefore, it is necessary to set the target SVV and conduct prospective trials to verify the safety margin for intraoperative management in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…SVV has been proposed as a predictor of fluid responsiveness 28 but the threshold at which SVV should trigger fluid administration during major liver resection remains a matter of debate. The SVV target cut-off used in our study (13%) is much lower than that reported by other research groups, who used cut-offs of 18 to 21% 29,30 and advocated using a high SVV as a safe alternative to CVP monitoring during hepatic transection. Two studies have compared the effects of targeting a high SVV (10 to 20%) vs. a low SVV (<10%) during hepatic resection 31,32 .…”
Section: Discussioncontrasting
confidence: 57%
“…SVV has been proposed as a predictor of fluid responsiveness 28 but the threshold at which SVV should trigger fluid administration during major liver resection remains a matter of debate. The SVV target cut-off used in our study (13%) is much lower than that reported by other research groups, who used cut-offs of 18 to 21% 29,30 and advocated using a high SVV as a safe alternative to CVP monitoring during hepatic transection. Two studies have compared the effects of targeting a high SVV (10 to 20%) vs. a low SVV (<10%) during hepatic resection 31,32 .…”
Section: Discussioncontrasting
confidence: 57%
“…More recently however, SVV has been proposed as a minimally invasive and more accurate metric for the dynamic assessment of intravascular volume status. The maintenance of a SVV in the range of 10–20% during major hepatic resection surgery has been shown to correlate with a low CVP [16], and there is growing consensus that targeting a high SVV may be a safe alternative to fluid therapy guided by CVP measurements [16,17]. The SVV target cut off used in our study is aligned with other research groups who report that a CVP between −1 and 1 mmHg strongly correlates to an SVV of 18%–21%; these authors advocate for using a high SVV as a safe alternative to CVP monitoring during hepatic transection [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…This value was set based on our considerations about SVV fluctuations in laparoscopic liver resection that we previously reported. 18 In actual intraoperative management, infusion volume was generally maintained at 2-4 mL/kg/h from start of anesthetic induction until completion of liver transection (the fluid restriction period). As a result, we achieved the target SVV (13%-20%) in all cases of the SVV group.…”
Section: Discussionmentioning
confidence: 99%